Impact of country’s governance dimensions on bank revenue efficiency: Overview on middle east, Southeast Asia, and South Asia countries - Hussain H.I.; Kamarudin F.; Anwar N.A.M.; Nassir A.M.; Sufian F.; Tan K.M. (Vilnius University, 2024)
Indexed by WOS/Scopus/ERA